Entrepreneurial Skills for Digital Journalist - Romero Echevarría, Martha Alicia (2016)
The socioeconomic impact has global effects and Media is not exempt from them as they follow global trends, leaving growing need evidence of the development of aptitudes and skills (personal and social) from Communication professionals, so that they are prepared to undertake their own projects either individually or collectively, with ability to plan and carry out with integrity and self-confidence and are able to persevere, especially in today’s digital environment, seeking to raise quality indexes, this means being able to achieve its objectives with responsibility, challenges in their performance and to control their reactions under pressure. In this sense for this research it has conducted an analysis of the entrepreneurial qualities of digital journalists for successful performance, which have their main source of vocational training to universities.